Short Paper Assignments - Pallas, Aaron (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This resource includes prompts for two short papers involving the following key concepts: individualizationof life course, sociological, imagination and the life course, transition to adulthood, linked lives